Analisis Laporan Keuangan Untuk Menilai Kinerja Perusahaan PT. Telekomunikasi Indonesia - Dharma, Budi; Lubis, Aulia Azmi; Hasibuan, Elda Anzeli (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This investigation focuses on PT Telekomunikasi Indonesia, Tbk's financial situation. After looking at the financial statements, financial ratios and the economic value added method (EVA) are used to measure it. The use of the internet and websites related to field research Data can be analyzed using quantitative data analysis. The accompanying ends can be drawn from the information examination in evaluating the monetary presentation of PT Telekomunikasi Indonesia, Tbk: 1) The organization's monetary exhibition, as estimated by proportions like liquidity, dissolvability and generally speaking benefit, obviously shows efficiency. There is still.2) Using the ratio of all positive calculation indicators to economic added value, good company products can also be identified.